Training on Making Media (Chemistry Online Learning) as a Distance Learning Solution - Rusly Hidayah; Kusumawati Dwiningsih; Utiya Azizah; Findiyanti Ernawati Asih (Warta Pengabdian, 2021)
The Covid 19 pandemic has hit all countries including Indonesia. Indonesia was hit by a pandemic starting in early March 2020. With this pandemic, Indonesia is required to be prepared for the potential spread of this virus. This is due to the geographical location of Indonesia which is directly adjacent to several countries affected by the spread of the Covid-19 virus as well as the development of globalization and increasingly smooth traffic between countries. One way to reduce the rate of spread of this virus is by implementing Large-Scale Social Restrictions (PSBB) so that all activities in schools and offices are carried out in a work from home (WFH) manner. Learning activities cannot be carried out directly so that learning in this period utilizes existing technology so that students still understand the material. As one solution to improving the quality of learning, the program activities make a product in the form of a learning video that is very interesting and fun so that students don't feel bored when participating in distance learning